A method for modifying the interface plasma cross-linking of the internal insulation of a composite insulator
Patent Information
- Application Number
- CN202611395773.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-09
- Publication Date
- 2026-10-23
AI Technical Summary
[0006]本发明的复合绝缘子内绝缘界面等离子体交联改性方法是一种兼顾“机械结合增强”与“电场均匀化”的双功能界面改性方案,可以解决传统湿化学偶联剂涂覆水解不均、与基体化学键合弱,导致芯棒-硅橡胶界面粘接强度不足的问题;还能避免芯棒-金具界面电场集中导致的高压端局部放电与发热;此外还避免了传统方法直接等离子体处理离子轰击过强,损伤基体表面且偶联剂易分解失活的问题
[0042]1)基体损伤小:本发明采用产生等离子体的放电核心区下游的芯棒改性区对复合绝缘子芯棒进行改性,改性过程中的活性物种以亚稳态粒子与自由基为主,离子轰击强度较直接等离子体处理大幅降低,避免了微裂纹与过度刻蚀,保障芯棒本体力学性能;
Smart Images

Figure CN122968076A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of high-voltage power transmission equipment manufacturing technology, and in particular to a method for plasma crosslinking modification of the internal insulation interface of composite insulators. Background Technology
[0002] Composite insulators consist of three parts: a glass fiber reinforced epoxy resin core rod, a silicone rubber sheath and skirts, and metal fittings at both ends. With their advantages of light weight, good resistance to flashover and easy maintenance, they have been widely used in high-voltage and ultra-high-voltage transmission lines.
[0003] However, the long-term operational reliability of composite insulators is highly dependent on the performance of their internal interfaces. There are two main types of interface problems: (1) Debonding problem of the core rod-silicone rubber sheath interface: The core rod and the silicone rubber sheath are usually bonded by co-vulcanization after coating with a coupling agent. Traditional processes often use wet chemical methods to directly brush or impregnate the silane coupling agent on the surface of the core rod, relying on the hydrolysis-condensation reaction of the coupling agent to bond with the matrix. This method has defects such as incomplete hydrolysis, poor coating uniformity, and weak chemical bonding with the core rod and silicone rubber. During operation, moisture can easily penetrate along the interface and form air gap defects at the interface. The air gap will cause interface discharge and heat generation under the action of electric field. In the long term, it will lead to interface deterioration, sheath scratches, and even induce core rod brittle fracture accidents. (2) Electric field concentration and partial discharge problem at the core rod-fitting interface: There is a significant change in dielectric constant and conductivity in the connection area between the high-voltage end fitting and the core rod of the composite insulator, which leads to severe local electric field distortion and easily causes partial discharge and corona discharge; the heat generated by partial discharge increases the temperature of the high-voltage end, accelerates material aging, and shortens service life. (3) Limitations of traditional plasma treatment: Plasma surface modification technology can introduce active groups and increase surface roughness without changing the chemical matrix, thereby improving the interfacial bonding force; for example, Chinese Patent Publication CN114217177A discloses a method for plasma etching of a mandrel using CF4 as working gas to improve interfacial bonding performance; Chinese Patent Publication CN119019813A discloses a technical solution for synergistic treatment of glass fiber with silane coupling agent and plasma; however, the above methods directly expose the material to the discharge core area (strong electric field area), and high-energy ions directly bombard the substrate surface, which has the following problems: ① Strong ion bombardment is prone to introducing microcracks or excessive etching on the mandrel surface, damaging the substrate; ② If the coupling agent directly enters the discharge core area, it is easily decomposed and deactivated by high-energy electrons, reducing the modification effect; ③ The uniformity of the treatment is affected by the field strength distribution in the discharge area, making it difficult to achieve uniform modification for complex shaped parts.
[0004] Therefore, there is an urgent need for an interface modification method and supporting materials that can efficiently initiate coupling agent modification without damaging the matrix surface. Summary of the Invention
[0005] This invention aims to at least solve one of the technical problems existing in the prior art. To this end, this invention provides a plasma crosslinking modification method for the interface of the inner insulation of a composite insulator. This interface modification method can improve the bonding strength between the composite insulator core rod and the silicone rubber sheath, and reduce partial discharge at the interface between the core rod and the high-voltage end fittings.
[0006] The plasma crosslinking modification method for the inner insulation interface of composite insulators of this invention is a dual-functional interface modification scheme that takes into account both "mechanical bonding enhancement" and "electric field homogenization". It can solve the problems of uneven hydrolysis and weak chemical bonding with the matrix caused by traditional wet chemical coupling agent coating, resulting in insufficient bonding strength of the core rod-silicone rubber interface; it can also avoid the partial discharge and heating of the high-voltage end caused by the electric field concentration at the core rod-fitting interface; in addition, it avoids the problems of excessive ion bombardment caused by direct plasma treatment in traditional methods, which damages the matrix surface and causes easy decomposition and deactivation of the coupling agent.
[0007] In a first aspect, the present invention provides a method for plasma crosslinking modification of the internal insulation interface of a composite insulator, including mandrel-silicone rubber interface modification and mandrel-fitting interface modification.
[0008] The mandrel-silicone rubber interface modification includes the following steps:
[0009] S1. The working gas is introduced into the discharge cavity of the plasma generating device, and radio frequency power is applied between the parallel plate electrodes to generate plasma; the adhesive coupling agent is carried by the carrier gas in the form of atomized droplets into the core rod modification area 10~25cm downstream of the parallel plate electrodes (discharge core area).
[0010] S2. The composite insulator core rod is placed in the core rod modification zone and modified by plasma and adhesive coupling agent to form an adhesive coupling agent modification layer on the surface of the core rod.
[0011] S3. Silicone rubber is coated on the silicone rubber bonding area of the mandrel, and then co-vulcanized to complete the mandrel-silicone rubber interface modification.
[0012] The mandrel-fitting interface modification includes the following steps:
[0013] S10, Steps S1 and S2 of modifying the mandrel-silicone rubber interface, forming an adhesive coupling agent modified layer on the surface of the mandrel;
[0014] S20. Apply a semiconductive coupling agent composition to the metal fitting connection area of the mandrel to form a semiconductive coupling agent coating.
[0015] S30. Assemble the mandrel and fittings, perform a pressing process, and then bake the mandrel. The semi-conductive coupling agent coating cross-links and cures to form a semi-conductive coupling agent layer, thus completing the mandrel-fitting interface modification.
[0016] The components of the semiconductive coupling agent composition include multi-walled carbon nanotubes, methyl vinyl silicone rubber raw rubber, silane coupling agent, and peroxide vulcanizing agent.
[0017] According to some embodiments of the present invention, after the entire mandrel is synchronously modified by plasma S1~S2, a semiconductive coupling agent layer is first prepared by S20~S30 on the metal fitting connection section at both ends. During this process, a protective sleeve is used to protect the middle section to avoid contamination of the semiconductive coupling agent. Then, the middle section is co-sulfurized by S3.
[0018] Furthermore, before proceeding with steps S20 to S30, a protective sleeve is fitted onto the middle section of the mandrel (the area to be bonded to the silicone rubber sheath). The protective sleeve is made of polytetrafluoroethylene and extends at least 5 cm beyond the area where the semiconductive coupling agent is applied. The protective sleeve is removed after steps S20 to S30 are completed. During removal, care should be taken to avoid damaging the already formed adhesive coupling agent modified layer.
[0019] According to some embodiments of the present invention, in step S1, the working gas includes argon, nitrogen, or a mixture of both.
[0020] According to some embodiments of the present invention, in step S1, applying radio frequency power between the parallel plate electrodes specifically refers to applying a sinusoidal voltage with a power of 50~300W, a peak voltage of 0.3~1.5kV, and a frequency of 10~20MHz.
[0021] According to some embodiments of the present invention, in step S1, the spacing between the parallel plate electrodes is 2~8cm, the distance between the left edge of the parallel plate electrodes and the left edge of the discharge cavity is 0~5cm, the height is located at the center of the discharge cavity, the width is 15~20cm, and the length is 0.5~3m (slightly longer than the core rod to be modified); the pressure of the discharge cavity is 10~100Pa.
[0022] The discharge core region is located between the parallel plate electrodes. The mandrel modification zone is situated 10-25 cm downstream of the gas outlet edge of the parallel plate electrodes within the discharge core region. The carrier gas and coupling agent atomized gas enter directly above the mandrel. To ensure uniform modification, the mandrel is placed on a rotating mechanism within the modification zone and rotates axially at a speed of 6-10 r / min. The discharge chamber pressure is regulated by a vacuum pump and its associated control system (maximum pumping speed ≥800 L / s, pressure control accuracy ±5 Pa; the vacuum pump and associated control and monitoring equipment used in this embodiment are commercially available).
[0023] According to some embodiments of the present invention, the ion density in the core rod modification region is lower than that in the discharge core region, and metastable particles (such as Ar*, N2*) are less abundant. Metastable species and free radicals (such as ·N) are the main active species; the metastable particle density in the core rod modification region can be controlled at 1×10⁻⁶ by adjusting the RF power, working gas flow rate and cavity pressure. 12 ~1×10 14 pcs / cm 3 Typical value is 1×10 12 ~1×10 13 pcs / cm 3 The free radicals in space are measured and fed back using laser-induced fluorescence analysis technology.
[0024] According to some embodiments of the present invention, the pure adhesive coupling agent is selected from at least one of γ-aminopropyltriethoxysilane (KH-550), vinyltriethoxysilane (A-151), and γ-glycidoxypropyltrimethoxysilane (KH-560); the purity is ≥99%; the adhesive coupling agent is liquid at room temperature and has low dynamic viscosity, and can be directly atomized without heating or solvent dilution, so it can be mechanically atomized into micron-sized droplets and carried into the modification zone by the carrier gas.
[0025] According to some embodiments of the present invention, the atomization method is as follows: a high-speed carrier gas jet impacts the pure coupling agent liquid flow or liquid film, shearing and breaking the liquid into atomized droplets; the carrier gas simultaneously serves as both the atomizing medium and the transport carrier gas; since pure silane coupling agents are easily hydrolyzed and condensed upon contact with water and thus become ineffective, the carrier gas used in the pure coupling agent room temperature atomization mode is dehumidified high-purity argon or nitrogen (purity ≥ 99.99%).
[0026] According to some embodiments of the present invention, the adhesive coupling agent is supplied at a rate of 0.5-10 mL / min, the atomized droplet size is 10-30 μm, the carrier gas includes argon, nitrogen, or a mixture of the two, the working gas flow rate is 15-25 L / min, and the carrier gas flow rate is 5-15 L / min; preferably, the adhesive coupling agent is supplied at a rate of 2-8 mL / min.
[0027] According to some embodiments of the present invention, in step S2, the plasma and adhesive coupling agent modification treatment time is 60~120s; and within 5h after the activation modification is completed, the co-sulfurization treatment described in step S3 or the application of the semiconductive coupling agent composition treatment in step S20 is performed; subsequent treatment is performed within a short time after activation modification to avoid the reduction of modification efficiency due to the recovery of surface inertia.
[0028] According to some embodiments of the present invention, the interval from activation completion to co-vulcanization is <5h; the temperature of the co-vulcanization treatment is 130~160℃ and the time is 8~12min; after co-vulcanization treatment, the active groups in the adhesive coupling agent modified layer participate in the vulcanization crosslinking of silicone rubber, forming a chemical bonding interface that runs through the three phases of mandrel → coupling agent → silicone rubber.
[0029] According to some embodiments of the present invention, in step S20, the components of the semiconducting coupling agent composition, by mass parts, include: 80-120 parts of methyl vinyl silicone rubber raw rubber, 5-15 parts of silane coupling agent, 4-12 parts of multi-walled carbon nanotubes, and 0.5-3 parts of peroxide vulcanizing agent.
[0030] According to some embodiments of the present invention, the silane coupling agent is at least one of γ-aminopropyltriethoxysilane (KH-550), vinyltriethoxysilane (A-151) or γ-glycidoxypropyltrimethoxysilane (KH-560).
[0031] According to some embodiments of the present invention, the molecular weight of the methyl vinyl silicone rubber raw rubber is 300,000 to 500,000, and the vinyl content is 0.05 to 0.5 mol.
[0032] According to some embodiments of the present invention, the multi-walled carbon nanotubes (MWNTs) are multi-walled carbon nanotubes surface-modified with a silane coupling agent, having a diameter of 10-30 nm, a length of 1-20 μm, a purity ≥95%, metal impurities ≤0.5%, and a silane coupling agent surface modification density of 0.5-2 μmol / m. 2 (Customization is available through the market).
[0033] According to some embodiments of the present invention, the peroxide vulcanizing agent may be selected from at least one of di-tert-butyl peroxide and 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane.
[0034] According to some embodiments of the present invention, the preparation method of the semiconductive coupling agent is as follows:
[0035] Methyl vinyl silicone rubber raw material and multi-walled carbon nanotubes are mixed and kneaded in a three-roll mill; a masterbatch with a multi-walled carbon nanotube mass fraction of 10%~25% is prepared; the masterbatch is mixed evenly with the remaining methyl vinyl silicone rubber raw material, silane coupling agent and peroxide vulcanizing agent.
[0036] Add the above materials to a planetary mixer and premix at a low speed of 500-600 r / min for 10-15 min (to prevent high viscosity from clumping). Then mix at a high speed of 1000-1200 r / min for 40-60 min, with the mixing temperature not exceeding 60℃. After mixing evenly, degas under vacuum for 10-15 min to obtain the semiconductive coupling agent.
[0037] According to some embodiments of the present invention, the volume resistivity of the semiconductive coupling agent layer is 1×10⁻⁶. 4 ~1×10 5 Ω·cm; preferably, the volume resistivity is 5×10 Ω·cm. 4 ~1×10 5 Ω·cm.
[0038] According to some embodiments of the present invention, the semiconductive coupling agent is pressed into a tablet (2 mm thick) at 0.8 MPa using the three-electrode method of GB / T 1410, and then crosslinked and cured by baking at 120~140℃ for 20~40 min. After naturally cooling to room temperature, the volume resistivity is measured and should fall within 1×10⁻⁶. 4 ~1×10 5 Within the range of Ω·cm; if outside this range, adjust the amount of masterbatch added or re-grind using the three-roll mill.
[0039] According to some embodiments of the present invention, in step S30, the stirred semiconductive paste is applied to the first layer of adhesive coupling agent modified layer at the interface between the fitting and the mandrel, with a thickness of 0.5~1mm. The pressing process is hydraulic pressing with a pressure of 10~30MPa. During pressing, excess semiconductive paste is squeezed out and should be wiped clean.
[0040] According to some embodiments of the present invention, in step S30, the baking process is as follows: after the pressing is completed, the metal fitting-core rod pressing part is placed in an oven and baked at 80~130℃ for 10~30 minutes to allow the semiconductive coupling agent coating to crosslink and cure, forming a semiconductive coupling agent layer.
[0041] The beneficial effects of this invention are:
[0042] 1) Minimal damage to the substrate: This invention uses a core rod modification zone downstream of the discharge core region that generates plasma to modify the composite insulator core rod. The active species in the modification process are mainly metastable particles and free radicals. The ion bombardment intensity is significantly reduced compared to direct plasma treatment, avoiding microcracks and excessive etching, and ensuring the mechanical properties of the core rod body.
[0043] 2) Uniform and efficient: In the method of the present invention, the adhesive coupling agent is introduced into the core rod modification zone in the form of atomized droplets by the carrier gas and simultaneously plasma-treated, and uniformly deposited on the surface of the core rod. This solves the problems of uneven hydrolysis and local accumulation in the traditional wet chemical method. The thickness of the modified layer is controllable and the distribution is uniform.
[0044] 3) Significantly reduced partial discharge at the mandrel-fitting interface: This invention uses the semiconducting properties of the second layer of carbon nanotube-based semiconducting coupling agent to homogenize the concentrated electric field near the fitting, forming a transition region between the non-conducting mandrel and the conductive fitting, thereby improving the partial discharge suppression effect.
[0045] 4) The composite insulator obtained by the modification method of this invention has excellent interfacial shear strength and resistance to boiling water aging, and excellent partial discharge initiation voltage and high-voltage end temperature rise performance; it significantly improves the bonding strength of the core rod-silicone rubber interface, which can better avoid partial discharge and heating of the high-voltage end caused by the concentration of electric field at the core rod-fitting interface.
[0046] 5) Strong process compatibility: The method of this invention can be integrated into a continuous production line for composite insulators, and has the prospect of industrial application.
[0047] Other features and advantages of the invention will be set forth in the description which follows, and will be apparent in part from the description, or may be learned by practicing the invention. Attached Figure Description
[0048] The present invention will be further described below with reference to the accompanying drawings and embodiments, wherein:
[0049] Figure 1 This is a schematic diagram of the plasma crosslinking modification device of the present invention;
[0050] Figure 2 This is a schematic diagram of the composite insulator structure of the present invention. Detailed Implementation
[0051] The following will describe the concept and technical effects of the present invention clearly and completely with reference to the embodiments, so as to fully understand the purpose, features and effects of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are all within the scope of protection of the present invention.
[0052] Unless otherwise specified in the examples, the procedures should be performed under standard conditions or conditions recommended by the manufacturer. Reagents or instruments whose manufacturers are not specified are all commercially available products.
[0053] Example 1
[0054] This embodiment provides a method for plasma crosslinking modification of the internal insulation interface of composite insulators.
[0055] 1. The steps of the plasma crosslinking modification method for the mandrel-silicone rubber interface are as follows:
[0056] 1) Apparatus Preparation: An radio frequency plasma device is used. The discharge chamber is equipped with parallel plate electrodes and a mandrel to be modified. The parallel plate electrodes form the core discharge region, with their left edges 3 cm from the left edge of the discharge chamber and located at the center of the chamber. The parallel plate electrodes are 3 cm apart, 18 cm wide, and 2.1 m long. The mandrel to be modified is located 15 cm downstream of the parallel plate electrodes. The inlet for the carrier gas and the atomized droplets of the binding coupling agent is directly above the mandrel. To ensure uniform modification, the mandrel is placed on a rotating mechanism within the modification zone. The device rotates axially at 6 r / min. The cavity is equipped with a vacuum pump and a mass flow controller. It also features a sealed atomizing liquid storage tank, a metering pump, and two-fluid atomizing nozzles. The atomizer and storage tank are sealed and moisture-proof. Five two-fluid atomizing nozzles, one for the adhesive coupling agent and one for the carrier gas, are located directly above the core rod and are evenly distributed axially. Five working gas nozzles are located directly to the left of the parallel plate electrode; the working gas enters the cavity through these nozzles, which are also evenly distributed axially. Two sets of nozzles are evenly distributed axially. A schematic diagram of the device is shown below. Figure 1 As shown;
[0057] 2) Plasma generation: High-purity Ar is used as the working gas with a flow rate of 20 L / min and a radio frequency power of 150 W. A sine wave with a peak radio frequency voltage of about 0.8 kV and a frequency of 13.56 MHz is applied between the electrodes. The parallel plate electrode spacing is 30 mm and the cavity pressure is 50 Pa to generate plasma.
[0058] 3) Atomization and delivery of the bonding coupling agent: Pure γ-aminopropyltriethoxysilane (KH-550, liquid with low viscosity at room temperature) was placed in a sealed storage tank and delivered to the two-fluid atomizing nozzles (5 nozzles, each with a flow rate of 1 mL / min) by a metering pump at a supply rate of 5 mL / min; high-purity dry Ar carrier gas was passed through the nozzles at a linear velocity of approximately 50 m / s and a flow rate of 5 L / min, shearing and breaking the pure KH-550 into atomized droplets (particle size approximately 20 μm) and entering the mandrel modification zone (15 cm downstream of the parallel plate electrode). At this point, the density of free radicals was measured to be 5.36 × 10⁻⁶. 12 pcs / cm 3 ;
[0059] 4) Mild modification reaction: The entire epoxy fiberglass core rod (12mm in diameter, FRP, 2m in length) is placed in the core rod modification zone. While the adhesive coupling agent atomizing nozzle is turned on, plasma treatment is performed for 90s to form the first adhesive coupling agent modified layer. In this method, the damage depth on the core rod surface is <1μm.
[0060] 2. The specific steps for plasma crosslinking modification of the mandrel-fitting interface are as follows:
[0061] The entire mandrel (including the metal fittings at both ends) is subjected to plasma crosslinking modification using the same process as steps 1) to 4) above to form the first layer of adhesive coupling agent modified layer (steps 1) to 4) have already been performed and will not be repeated).
[0062] 5) Preparation of semiconductive coupling agents:
[0063] Take 100 parts of methyl vinyl silicone rubber raw rubber (molecular weight 300,000-500,000, vinyl content 0.05-0.5 mol%) and modify MWNTs (diameter 10-30 nm, length 1-20 μm, purity ≥95%, metal impurities ≤0.5%, silane coupling agent surface modification density 1 μmol / m) with KH-550. 2 20 parts of powder were placed in a three-roll mill (roller diameter 150~200mm) for mixing. The roller gaps were set sequentially as follows: first gap 100μm, speed ratio (front:middle:rear = 1:3:9) to generate high shear due to the difference in linear velocity; second gap 50μm; third gap 20μm; fourth (fine dispersion): gap 10μm; the roller temperature was controlled between 30~40℃ throughout the process (to prevent premature cross-linking of raw rubber). The milling was carried out for 5 passes until the paste was visually free of obvious particles. A sample was taken for SEM cross-sectional inspection (10000x magnification) to confirm that there were no obvious agglomerates of MWNT (agglomerate size ≤500nm); a masterbatch with a mass fraction of 16.7% MWNT (KH-550 modified) was obtained.
[0064] Take the above masterbatch and mix it with fresh raw rubber according to the proportions in Table 1 below to prepare a semiconductive coupling agent composition:
[0065] Add the above materials to a planetary mixer, premix at a low speed of 500 r / min for 10 min (to prevent high viscosity from clumping), then mix at a high speed of 1100 r / min for 50 min, with a mixing temperature of 55℃ (not exceeding 60℃); after mixing evenly, degas under vacuum for 15 min to obtain a semiconductive coupling agent paste.
[0066] 6) Application of semiconductive coupling agent: Apply the paste to the first layer of adhesive coupling agent modification layer at the interface (both ends) between the fitting and the mandrel, with a thickness of 0.8 mm;
[0067] 7) Crimping: Insert the two ends coated with the semi-conductive coupling agent into the aluminum alloy fitting and crimp them hydraulically at a pressure of approximately 20 MPa.
[0068] 8) Baking: Place the metal fitting-core crimping part in an oven and bake at 125℃ for 30 minutes to form a second layer of semi-conductive coupling agent;
[0069] 9) Sheath vulcanization: After the end fittings are pressed and baked, the middle section of the modified mandrel that needs to be bonded to the silicone rubber sheath is covered with HTV high-temperature vulcanized silicone rubber by injection / molding, and then co-vulcanized at 150℃ for 10 minutes to form a chemical bonding interface.
[0070] The interval between the formation of the first adhesive coupling agent modified layer and the vulcanization treatment should be less than 5 hours to avoid the surface chemical bonds from reacting with gaseous dust in the air and causing failure.
[0071] A schematic diagram of the composite insulator structure of the present invention is shown below. Figure 2 As shown.
[0072] Example 2
[0073] This embodiment provides a method for plasma crosslinking modification of the internal insulation interface of a composite insulator. The crosslinking modification method of the core rod and silicone rubber interface in this embodiment is basically the same as that in Embodiment 1, except that N2 is used instead of Ar as the working gas in this embodiment.
[0074] Specifically, in step 2) of this embodiment: high-purity N2 is used as the working gas with a flow rate of 25L / min, radio frequency power of 180W, a sine wave with a peak radio frequency voltage of about 1kV and a frequency of 13.56MHz is applied between the electrodes, the parallel plate electrode spacing is 30mm, the cavity pressure is 50Pa, and plasma is generated.
[0075] In step 3), Ar carrier gas is replaced with N2 carrier gas.
[0076] In this embodiment, the N2 plasma core rod modification region generates N free radicals and metastable states. Particles can also achieve surface activation and coupling agent modification.
[0077] The plasma crosslinking modification of the mandrel-fitting interface in this embodiment is basically the same as that in Example 1. The difference is that in this embodiment, the number of multi-walled carbon nanotubes in the semiconductive coupling agent in step 5) is adjusted to 15 parts, and the remaining process parameters and methods are the same as those in Example 1.
[0078] Comparative Example 1
[0079] The core rod-silicone rubber interface modification of the comparative composite insulator was carried out using the traditional wet chemical coupling agent coating method:
[0080] The same adhesive coupling agent as in step 3 of Example 1 was directly applied to the surface of the mandrel, dried at room temperature for 30 minutes, and then co-cured with the HTV silicone rubber sheath (using the same method and parameters as in Example 1); no plasma activation or modification steps were performed.
[0081] In this comparative example, the mandrel-fitting interface is directly press-fitted without the use of any coupling agent.
[0082] Comparative Example 2
[0083] This comparative example is basically the same as Example 1, except that in this comparative example, the core rod is placed directly in the discharge core area (strong electric field area) for strong ion bombardment treatment. The core rod is located at the right exit of the parallel plate electrode (0 cm away from the parallel plate electrode), and the inlet of the carrier gas and coupling agent atomized droplets is located directly above the core rod.
[0084] The process was performed using the same process parameters as in Example 1: power (150W), voltage (approximately 0.8kV), frequency (13.56MHz), and time (90s).
[0085] Comparative Example 3
[0086] This comparative example is basically the same as Example 2, except that in the semiconductive coupling agent of this comparative example, ZnO micro-nano powder (particle size 20μm+particle size 150nm, mass ratio 1:1) is used instead of carbon nanotubes.
[0087] Comparative Example 4
[0088] This comparative example is basically the same as Example 1, except that the core rod in this comparative example is activated by plasma in the core rod modification zone (parameters are the same as in Example 1), but the adhesive coupling agent is not treated by the atomized droplets in Example 1, but is directly applied after plasma activation to form a physical adsorption layer with the same amount of adhesive coupling agent.
[0089] The above embodiments and comparative examples yielded composite insulators with a voltage rating of 220kV. The experimental design and statistical data are explained below:
[0090] All embodiments and comparative examples follow a unified experimental design and data statistics rule, as detailed below:
[0091] 1) Sample batches and quantities: For each example / comparative example, 5 groups of samples with 3 pieces per group (n=15) were prepared under the same process conditions for interfacial shear strength, PDIV (partial discharge initiation voltage), high-voltage end temperature rise and volume resistivity testing (for hardware-mandrel related tests, press-fitted assembly samples were used), and the test results were averaged; for the water boiling aging test, another 3 groups with 3 pieces per group (n=9) were selected, and the interfacial shear strength was measured before and after aging and the retention rate was calculated, and the results were averaged; for the surface damage depth (roughness Ra) test, 5 pieces were randomly selected from the same batch of samples, and 5 measuring points were taken for each piece, and the average value was taken.
[0092] 2) Testing instruments and methods:
[0093] Interfacial shear strength: Universal testing machine (such as Instron 5967 type), modified according to GB / T7124, the specimen is subjected to mandrel-shear double lap shear, and the crossover speed is 2mm / min;
[0094] Boiling water retention rate: According to IEC62217, the residual interfacial shear strength of the sample is measured after boiling in water for 96 hours. Retention rate = shear strength after aging / shear strength before aging × 100%;
[0095] Surface damage depth (roughness Ra): Atomic force microscopy (AFM), tested according to ISO 13095-2014 standard, and the average value of 5 points was taken;
[0096] Partial discharge initiation voltage (PDIV): Measured with a partial discharge tester according to IEC60270, with a voltage ramp rate of 1kV / s. Record the discharge initiation voltage. The insulator is not equipped with an equalizing ring.
[0097] High-voltage end temperature rise: K-type thermocouple + data logger, the thermocouple is attached to the outer surface of the high-voltage end fitting, and the steady-state temperature rise is recorded after rated operation to steady state (≥4h);
[0098] Volume resistivity of the semiconducting layer: Measured using a high-resistivity meter (such as Keithley 6517B) via the three-electrode method, according to GB / T1410. The semiconducting coupling agent paste is pressed into a tablet (2 mm thick) at 0.8 MPa, baked at 130℃ for 30 min for cross-linking and curing, and then naturally cooled to room temperature before measuring the volume resistivity.
[0099] The test results are shown in Table 2:
[0100] The results above show that, compared with the traditional wet chemical method (Comparative Example 1), the modified technical solutions of the present invention (Examples 1 and 2) are significantly different. In Comparative Example 1, the silane coupling agent was directly brushed onto the core rod surface. Pure KH-550 has a high surface tension (approximately 30-40 mN / m), while the FRP core rod surface has a certain degree of roughness. Direct brushing makes it difficult for the coupling agent to spread evenly on the core rod surface, resulting in discontinuous droplets or spots. This weakens its penetration and filling ability into the surface microstructure, leading to poor modification effects. The shear strength is only 8.5 MPa (61.6% of Example 1), and the water boiling retention rate is 64% (72.7% of Example 1). Simultaneously, the direct pressing of the fitting-core rod interface lacks a semiconductive layer, resulting in a concentrated electric field at the high-voltage end that cannot be alleviated. This leads to a PDIV of only 138.2 kV (85.7% of Example 1), while the temperature rise reaches 5.1 K (2.8 times that of Example 1), making it significantly inferior to the composite insulator prepared in the embodiments of the present invention.
[0101] Compared with the direct core region plasma modification method (Comparative Example 2), the embodiments of the present invention involve placing the core rod directly in the discharge core region (strong electric field region) and treating it with the same power (150W), voltage (approximately 0.8kV), and time (90s). The high-energy plasma directly bombards the core rod surface, causing severe molecular chain breakage and microcracks. Therefore, the surface damage depth is as high as 8μm (10.7 times that of Example 1), the shear strength is only 10.3MPa, and the water boiling retention rate is only 71%, resulting in overall performance lower than the embodiments of the present invention.
[0102] Compared to the method using ZnO (Comparative Example 3), which uses multi-walled carbon nanotubes, Comparative Example 3 uses ZnO micro / nano powder instead of multi-walled carbon nanotubes in a semiconductive coupling agent. Due to the insufficient conductivity of ZnO itself, the resistivity is still as high as 4.1 × 10⁻⁶ parts per 40 parts. 5 Ω·cm, which is the value of Example 1 (8.5 × 10⁻⁶). 4 The resistivity is 4.8 times that of the mandrel-fitting interface; the excessively high resistivity leads to a serious decrease in the electric field homogenization effect, with PDIV dropping from 161.2kV to 158.1kV and the temperature rise increasing from 1.8K to 3.0K, demonstrating the superiority of the embodiment.
[0103] Compared with the method of directly applying the adhesive coupling agent to the activated mandrel (Comparative Example 4), the atomized droplet modification method of the present invention: Comparative Example 4 first activated the mandrel surface with plasma, and then directly applied the adhesive coupling agent to the activated mandrel surface. It was impossible to form a dense and uniform chemical bonding interface as in the example, resulting in a shear strength of only 10.2 MPa (74% of Example 1) and a water boiling retention rate of only 75% (85% of Example 1). This shows the significant advantage of the atomization-based modification method of the present invention in terms of interface uniformity.
[0104] The embodiments of the present invention have been described in detail above. However, the present invention is not limited to the above embodiments. Within the scope of knowledge possessed by those skilled in the art, various changes can be made without departing from the spirit of the present invention. Furthermore, the embodiments of the present invention and the features thereof can be combined with each other unless otherwise specified.
Claims
1. A method for plasma crosslinking modification of the internal insulation interface of a composite insulator, characterized in that, This includes mandrel-silicone rubber interface modification and mandrel-fitting interface modification; The mandrel-silicone rubber interface modification includes the following steps: S1. The working gas is introduced into the discharge cavity of the plasma generating device, and radio frequency power is applied between the parallel plate electrodes to generate plasma; the adhesive coupling agent is carried by the carrier gas in the form of atomized droplets into the core rod modification zone 10~25cm downstream of the parallel plate electrodes. S2. The composite insulator core rod is placed in the core rod modification zone and modified by plasma and adhesive coupling agent to form an adhesive coupling agent modification layer on the surface of the core rod. S3. Silicone rubber is coated on the silicone rubber bonding area of the mandrel, and then co-vulcanized to complete the mandrel-silicone rubber interface modification. The mandrel-fitting interface modification includes the following steps: S10, Steps S1 and S2 of modifying the mandrel-silicone rubber interface, forming an adhesive coupling agent modified layer on the surface of the mandrel; S20. Apply a semiconductive coupling agent composition to the metal fitting connection area of the mandrel to form a semiconductive coupling agent coating. S30. Assemble the mandrel and fittings, perform a pressing process, and then bake the mandrel. The semi-conductive coupling agent coating cross-links and cures to form a semi-conductive coupling agent layer, thus completing the mandrel-fitting interface modification. The components of the semiconductive coupling agent composition include multi-walled carbon nanotubes, methyl vinyl silicone rubber raw rubber, silane coupling agent, and peroxide vulcanizing agent.
2. The plasma crosslinking modification method for the internal insulation interface of a composite insulator according to claim 1, characterized in that, In step S1, the working gas includes argon, nitrogen, or a mixture of both; and / or, The application of radio frequency power between the parallel plate electrodes specifically refers to applying a sinusoidal voltage with a power of 50~300W, a peak voltage of 0.3~1.5kV, and a frequency of 10~20MHz.
3. The plasma crosslinking modification method for the internal insulation interface of a composite insulator according to claim 1, characterized in that, In step S1, the spacing between the parallel plate electrodes is 2~8cm, and the discharge chamber pressure is 10~100Pa; and / or, The adhesive coupling agent is supplied at a rate of 0.5–10 mL / min, and the atomized droplet size is 10–30 μm. The carrier gas includes dehumidified high-purity argon, nitrogen, or a mixture of both; and / or, The flow rate of the working gas is 15~25L / min, and the flow rate of the carrier gas is 5~15L / min.
4. The plasma crosslinking modification method for the internal insulation interface of a composite insulator according to claim 1, characterized in that, In step S1, the adhesive coupling agent includes at least one of γ-aminopropyltriethoxysilane, vinyltriethoxysilane, or γ-glycidoxypropyltrimethoxysilane.
5. The plasma crosslinking modification method for the internal insulation interface of a composite insulator according to claim 1, characterized in that, In step S2, the plasma and adhesive coupling agent modification treatment time is 60-120 s; and / or, Within 5 hours after step S2 is completed, proceed with either step S3 or step S20.
6. The plasma crosslinking modification method for the internal insulation interface of a composite insulator according to claim 1, characterized in that, In step S20, the components of the semiconducting coupling agent composition, by mass parts, include: 80-120 parts of methyl vinyl silicone rubber raw rubber, 5-15 parts of silane coupling agent, 4-12 parts of multi-walled carbon nanotubes, and 0.5-3 parts of peroxide vulcanizing agent.
7. The plasma crosslinking modification method for the internal insulation interface of a composite insulator according to claim 6, characterized in that, The silane coupling agent is at least one selected from γ-aminopropyltriethoxysilane, vinyltriethoxysilane, or γ-glycidoxypropyltrimethoxysilane; and / or The peroxide vulcanizing agent is di-tert-butyl peroxide or 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane; and / or, The multi-walled carbon nanotubes are multi-walled carbon nanotubes surface-modified with a silane coupling agent, with a diameter of 10~30 nm and a length of 1~20 μm; and / or, The methyl vinyl silicone rubber raw material, silane coupling agent, multi-walled carbon nanotube powder, and peroxide vulcanizing agent are mixed to obtain the semiconductive coupling agent composition.
8. The plasma crosslinking modification method for the internal insulation interface of a composite insulator according to claim 7, characterized in that, The semiconductive coupling agent composition is prepared by a two-step mixing method using a masterbatch method: first, multi-walled carbon nanotubes and methyl vinyl silicone rubber raw rubber are mixed by a three-roll milling method to prepare a masterbatch with a multi-walled carbon nanotube mass fraction of 10% to 25%; then, the masterbatch is mixed evenly with the remaining methyl vinyl silicone rubber raw rubber, silane coupling agent, and peroxide vulcanizing agent.
9. The plasma crosslinking modification method for the internal insulation interface of a composite insulator according to claim 1, characterized in that, In step S30, the crimping process is hydraulic crimping, with a pressure of 10~30MPa; and / or, The baking process is as follows: after the pressing is completed, the metal fitting-mandrel pressing part is placed in an oven and baked at 80~130℃ for 10~30 minutes to allow the semiconductive coupling agent coating to crosslink and cure, forming a semiconductive coupling agent layer.
10. The plasma crosslinking modification method for the internal insulation interface of a composite insulator according to claim 1, characterized in that, The volume resistivity of the semiconductive coupling agent layer is 1×10⁻⁶. 4 ~1×10 5 Ω·cm.
Citation Information
Patent Citations
Method for improving interface performance of composite insulator
CN114217177A
Modified glass fiber reinforced epoxy resin composite material and preparation method thereof
CN119019813A